РЕЗУЛЬТАТЫ ОЦЕНКИ ЦИТОГЕНЕТИЧЕСКОГО СТАТУСА У МУЖЧИИ ИЗ ДВУХ ВЬЕТНАМСКИХ ДЕРЕВЕНЬ С РАЗНОЙ ЭКОТОКСИКОЛОГИЧЕСКОЙ СИТУАЦИЕЙ - Н.В., Умнова; Л.П., Сычева; М.А., Коваленко; В.С., Журков; В.С., Румак; Во, Вьет Кыонг; Фам, Кхак Линь (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
CYTOGENETIC STATUS INVESTIGATION AMONG TWO MALE GROUPS FROM VILLAGES WITH DIFFERENT ECOTOXICOLOGICAL SITUATIONHuman epidemiological and clinical studies demonstrated development of dioxin pathology among population living in the ecocide area - territory sprayed with Agent Orange almost 40 years ago. Strengthening of destructive processes’ effects in mucous epithelial cells (membranes) among residents of dioxin- contaminated territory indicated obvious changes in regulation of cell cycle and apoptosis, and in situation of population chronic exposure to low doses of dioxins this could modify systemic effects and affect the health and reactivity.